PELATIHAN DAN PENDAMPINGAN KADER KESEHATAN DALAM PENGELOLAAN PENYAKIT HIPERTENSI DI KELURAHAN BANDUNG KOTA TEGAL - Suparjo Suparjo; Fatchurrozak Himawan; Nurcholis - (Poltekkes Kemenkes Semarang, 2024)
One of the non-communicable diseases that many people suffer from is hypertension. Hypertension is a silent disease, because sufferers do not know that they suffer from this disease before having their blood pressure checked. There is a risk of more serious illnesses such as stroke, heart attack and heart failure if you do not receive immediate treatment. In the current era of the COVID 19 pandemic, hypertension sufferers are a group that is at high risk of experiencing severity and can even cause death. Health cadres and families have a very important role in monitoring the health status of hypertension sufferers, especially in managing hypertension. Hypertension sufferers' problems that occur over a long period of time and continuously can trigger strokes, heart attacks, heart failure and are the main cause of chronic kidney failure. Therefore, hypertension management is needed to prevent damage to target organs in the long term thereby reducing morbidity and mortality. The methods used are education, training and mentoring of health cadres and families as role models and change agents in the community to increase knowledge and abilities through education and management training. hypertension. The result of this community service is an increase in health cadres' knowledge of the management of hypertension.